Effect of Different Rates of Nitrogen Fertilization on Crop Yield, Soil Properties and Leaf Physiological Attributes in Banana Under Subtropical Regions of China - Sun, Jianbo; Li, Wenbin; Li, Chunqiang; Chang, Wenjun; Zhang, Shiqing; Zeng, Yanbo; Zeng, Changying; Peng, Ming (Frontiers in Plant Science, 2020)
Excessive nitrogen (N) application is widespread in Southern China. The effects of N fertilization on soil properties and crop physiology are poorly understood in tropical red loam soil. We conducted a field experiment to evaluate the effect of nitrogen fertilization rates on physiological attributes (chlorophyll, plant metabolic enzymes, soluble matters) on banana leaves, soil properties (soil enzymes, soil organic matter (SOM), soil available nutrients) as well as banana crop yield in a subtropical region of southern China. The N rates tested were 0 (N0), 145 (N145), 248 (N248), 352 (N352), 414 (NFT), and 455 (N455) g N per plant. The correlations among soil factors, leaf physiological factors and crop yield were evaluated. The results indiated that the high rates of N fertilization (NFT and N455) significantly decreased soil available potassium (K) content, available phosphorus (P) content, glutamine synthetase (GS) activity, and soluble protein and sugar contents compared with lower N rates. The N352 treatment had the highest crop yields compared with higher N rates treatments, followed by the N455 treatment. However, there were no significant differences in crop yields among N fertilization treatments. Factor analysis showed that the N352 treatment had the highest integrated score for soil and leaf physiological factors among all treatments. Moreover, the N352 treatment was the most effective in improving carbon and nitrogen metabolism in banana. Crop yield was significantly and positively linearly correlated with the integrated score (r = 0.823, p < 0.05). Path analysis revealed that invertase, SOM and sucrose synthase (SS) had a strong positive effect on banana yield. Canonical correspondence analysis (CCA) suggested that available K, invertase, acid phosphatase and available P were the most important factors impacting leaf physiological attributes. Cluster analysis demonstrated distinct differences in N application treatment related to variations in soil and leaf factors. This study suggested that excessive N fertilization had a negative effect on soil fertility, crop physiology and yield. The lower N rates were more effective in improving crop yield than higher rates of N fertilization. The N rate of 352 g N per plant (N352) was recommended to reduce excess N input while maintaining the higher yield for local farmers’ banana planting.